KERENTANAN BANJIR BANDANG DI SUB DAS MALALO KECAMATAN BATIPUH SELATAN KABUPATEN TANAH DATAR - agussalim, apriadi; triyatno, triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
The Malalo Sub-watershed, South Batipuh District, Tanah Datar Regency is one area that is often hit by flash floods. The purpose of this study was to assess the vulnerability of flash floods disasters in the Malalo sub-watershed, South Batipuh sub-district. The flash flood disaster vulnerability analysis refers to the parameters of the Head of BNPB Regulation No. 2 of 2012 concerning General Guidelines for Disaster Risk Assessment. The social vulnerability of the flash floods disaster consists of social vulnerability, economic vulnerability, physical vulnerability and environmental vulnerability. The results of the vulnerability analysis are: Social vulnerability consists of population density with low vulnerability, sex ratio with high vulnerability, poverty ratio with low vulnerability, ratio of disabled people with low vulnerability and age group ratio with high vulnerability. Economic vulnerability consists of productive land with a low level of vulnerability and GRDP with a high level of vulnerability. Physical vulnerability consists of the total price of houses with a high level of vulnerability, the total price of public facilities is categorized as high and critical facilities are categorized as high. Environmental vulnerability consists of protected forest area with a high level of vulnerability, production forest with a high level of vulnerability and shrubs with a low level of vulnerability.